Redox-based epigenetic status in drug addiction: a potential contributor to gene priming and a mechanistic rationale for metabolic intervention - Trivedi, Malav S.; Deth, Richard (Frontiers in Neuroscience, 2015)
Alcohol and other drugs of abuse, including psychostimulants and opioids, can induce epigenetic changes: a contributing factor for drug addiction, tolerance, and associated withdrawal symptoms. DNA methylation is a major epigenetic mechanism and it is one of more than 200 methylation reactions supported by methyl donor S-adenosylmethionine (SAM). Levels of SAM are controlled by cellular redox status via the folate and vitamin B12-dependent enzyme methionine synthase (MS). For example, under oxidative conditions MS is inhibited, diverting its substrate homocysteine (HCY) to the trans sulfuration pathway. Alcohol, dopamine, and morphine, can alter intracellular levels of glutathione (GSH)-based cellular redox status, subsequently affecting SAM levels and DNA methylation status. Here, existing evidence is presented in a coherent manner to propose a novel hypothesis implicating the involvement of redox-based epigenetic changes in drug addiction. Further, we discuss how a “gene priming” phenomenon can contribute to the maintenance of redox and methylation status homeostasis under various stimuli including drugs of abuse. Additionally, a new mechanistic rationale for the use of metabolic interventions/redox-replenishers as symptomatic treatment of alcohol and other drug addiction and associated withdrawal symptoms is also provided. Hence, the current review article strengthens the hypothesis that neuronal metabolism has a critical bidirectional coupling with epigenetic changes in drug addiction exemplified by the link between redox-based metabolic changes and resultant epigenetic consequences under the effect of drugs of abuse.